Impact of expiratory strength training in amyotrophic lateral sclerosis: Results of a randomized, sham‐controlled trial. Issue 1 (29th November 2018) - Plowman, Emily K.; Tabor‐Gray, Lauren; Rosado, K. Michelle; Vasilopoulos, Terrie; Robison, Raele; Chapin, Jennifer L.; Gaziano, Joy; Vu, Tuan; Gooch, Clifton
ABSTRACT: Introduction: The purpose of this study was to determine the impact of an in‐home expiratory muscle strength training (EMST) program on pulmonary, swallow, and cough function in individuals with amyotrophic lateral sclerosis (ALS). Methods: EMST was tested in a prospective, single‐center, double‐blind, randomized, controlled trial of 48 ALS individuals who completed 8 weeks of either active EMST ( n = 24) or sham EMST ( n = 24). The primary outcome to assess treatment efficacy was change in maximum expiratory pressure (MEP). Secondary outcomes included: cough spirometry; swallowing; forced vital capacity; and scoring on the ALS Functional Rating Scale—Revised. Results: Treatment was well tolerated with 96% of patients completing the protocol. Significant differences in group change scores were noted for MEP and Dynamic Imaging Grade of Swallowing Toxicity scores ( P < 0.02). No differences were noted for other secondary measures. Discussion: This respiratory training program was well‐tolerated and led to improvements in respiratory and bulbar function in ALS. Muscle Nerve 59 :40–46, 2019 Abstract : See editorial on pages 6–7 in this issue .